U źródeł historii wychowania na ziemiach polskich - Meissner, Andrzej (Biuletyn Historii Wychowania, 2023)
The article revolves around the history of upbringing in Poland as a science discipline. The first historical-pedagogical works appeared in the Renaissance and were continued in Age of Enlightenment. However, it was not until the-19th century when a discipline called ‘history of upbringing’ was created. Its development, by East European standards, took place in difficult social and political circumstances. Poland, at that time annexed by Russia, Prussia and Austria, did not enjoy conditions conducive to scientific development. The annexation was counterbalanced by actions instigated by cultural, educational and scientific institutions. As a result, historical science could develop despite the political situation and the financial shortcomings. Introduction of pedagogy and history of upbringing at the Krakow and Lvov Universities was important to the development of the history of upbringing. Antoni Karbownik’s post-doctoral degree in the history of upbringing obtained in 1905 from the Jagiellonian University and post-doctoral degrees in pedagogy (also the Jagiellonian University) awarded to Leon Kulczyński, Euzebiusz Czerkawski, Aleksander Skórski, Antoni Danysz and Bolesław Mańkowski (Lvov University) were breakthroughs in the history of upbringing. For the areas of study to become disciplines of science, they had to be defined, including their research object and the methodological basis. Władysław Seredyński Franciszek Majchrowicz, Antoni Karbowiak and Antoni Danysz adopted a position on the subject. In the late 19th and the early 20th centuries the history of upbringing was perceived as a discipline of science related to history with respect to the ,methodology and with pedagogy with respect to the content, with its own research, terminology, sources and academic teachers. The history of education was officially a part of culture. In this context, educational matters should be viewed.